BIOTECHNOLOGY RESEARCH AND DEVELOPMENT SYSTEM OF CLINICAL NUTRITION IN HOSPITAL - R. R. Hamidova (Вестник Дагестанского государственного технического университета: Технические науки, 2016)
Discussed the organization of clinical nutrition at the hospital. Give a general idea of biotechnological systems. Developed a method of therapeutic feeding in the hospital using biotechnical systems for medical purposes.